Knowledge And Attitude Among Non-critical Patients Of The Emergency Unit At The Besut District Health Clinics - Hafiz Abdullah, Mohd Amirul; Awang, Hafizuddin (International Journal of Human and Health Sciences (IJHHS), 2024)
Introduction: In the primary healthcare system, the Emergency Unit of the Besut District HealthClinic serves as the primary entry point for urgent medical care, which is an important functionthat the emergency unit service provides. For the purpose of improving healthcare outcomes andmaking the most efficient use of available resources, it is essential to have an understanding of thepatient’s knowledge and attitudes toward this emergency unit. Materials and Methods: Patientswho were treated at the Besut District Health Clinic Emergency Unit were the subjects of thestudy, and the researchers collected data from them through a variety of approaches, includingquestionnaires, interviews, and data gathering. The use of this all-encompassing methodologymade it possible to conduct an in-depth investigation of the opinions and experiences of patients.Results: Various levels of patient knowledge regarding the appropriate utilization of emergencycare and the services that are offered were discovered by the study. Patients presented a varietyof viewpoints regarding the quality of care and communication between patients and providers.There is space for development in patient-centered care and communication tactics, as evidencedby the fact that some patients reported having great experiences while others expressed concerns.Conclusion: The results indicate that the overall efficiency of the Emergency Unit falls short of thepredetermined KPI. Targeted educational efforts, such as informative brochures and workshops,are necessary to enhance patient comprehension of the functions and capabilities of the EmergencyUnit. Furthermore, the study emphasizes the significance of improving protocols, staff education,and communication between patients and healthcare providers in order to narrow the dividebetween patient expectations and healthcare services. These enhancements possess the capacity toaugment patient contentment, optimize healthcare results, and raise the overall effectiveness of thehealthcare system. International Journal of Human and Health Sciences Vol. 08 No. 04 Oct’24 Page: 341-347